DUKUNGAN SOSIAL ORANG TUA TUNGGAL (SINGLE PARENTS) PADA ORANG DENGAN SKIZOFRENIA (ODS) DI KELURAHAN CIGONDEWAH RAHAYU KECAMATAN BANDUNG KULON KOTA BANDUNG - Brelyantika Indra Jesa; Uke Hani Rasalwati; Ajat Sudrajat Kurnia (Indonesian Journal of Social Work, 2021)
Social support consists of emotional, rewarding, instrumental, and informative support given by people around individuals to overcome problems and crises in the life of one of the families. Social support can affect a person's mental and physical health, so people with schizophrenia (ODS) really need it. The purpose of this study is to see how single parents in Cigondewah Rahayu Village, Bandung Kulon District, Bandung City still provide social support to People With Schizophrenia (ODS) with existing limitations. This study used a descriptive qualitative method with four informants consisting of two single fathers and single mothers. The results showed that single parents provide social support to person with schizofrenia which provides emotional, rewarding, instrumental and informative support. However, the aspect of instrumental support, particularly health, is still lacking and informative support is low. In providing social support, single mothers provide greater support than the figure of single fathers who have to work so that there are other figures who help such as grandmothers, or other family members.